Esclerosis Tuberosa - López Flores, Linda Julissa; Caballero Castro, Héctor Rubén (Acta Pediátrica Hondureña, 2017)
No hay Resumen Acta Pediátrica Hondureña, Vol. 6, No. 2 /octubre 2015 a marzo 2016: 493